THE GROWTH PERFORMANCE AND DIGESTIBILITY OF TENEBRIO MOLITOR FED WITH TWO DIFFERENT DIETS - Polovinski-Horvatović, Miroslava (Food and Feed Research, 2024)
Tenebrio molitor is an easily obtained highly nutritional alternative source of protein in animal feed. To get good results in growth performance and nutritional composition, it is necessary to know the diet digestibility and dietary needs of T. molitor. In the experimental condition, the T. molitor was fed with wheat bran and oat flakes, two easily accessible diets on the local market at an acceptable price. Both groups (four replicates each) of T. molitor were fed the same diet weekly (25 g of feed and water were supplied through agar). The production parameters such as feed conversion, intake of feed, and growth during the whole experimental period were observed. At the same time, the digestibility study was performed to obtain the coefficient of digestibility of the dry matter, organic matter, ash, crude protein, crude fat, neutral detergent fibre (NDF), acid detergent fibre (ADF), and hemicelluloses. For both diets, the growth parameters were relatively similar having been slightly better for the oat flakes. The feed conversion ratio for wheat bran and oat flakes was 2.16 and 2.00, with growth per unit average of 46.37 g and 50.30 g respectively. The digestibility trial showed much better digestibility of oat flakes with the average digestibility coefficient of dry matter of 0.78, organic matter 0.80, crude protein 0.46, and crude fat 0.85. The digestibility of wheat bran was for dry matter 0.50, organic matter 0.51, crude protein 0.33, and crude fat 0.88. Both diets can be successfully used for the nutritional needs of T. molitor, however, using the oat flakes gives better growth performance and digestibility results. The choice of the diet will depend on the costs at the moment.
Keywords: mealworm beetle; feed conversion; coefficient of digestibility; wheat bran diet; oat flakes diet